Altered Expression of Endoplasmic Reticulum Stress Associated Genes in Hippocampus of Learned Helpless Rats: Relevance to Depression Pathophysiology - Timberlake, Matthew A.; Dwivedi, Yogesh (Frontiers in Pharmacology, 2016)
The unfolded protein response (UPR) is an evolutionarily conserved defensive mechanism that is used by cells to correct misfolded proteins that accumulate in the endoplasmic reticulum. These proteins are misfolded as a result of physical stress on a cell and initiate a host of downstream effects that govern processes ranging from inflammation to apoptosis. To examine whether UPR system plays a role in depression, we examined the expression of genes that are part of the three different pathways for UPR activation, namely GRP78, GRP94, ATF6, XBP-1, ATF4 and CHOP using an animal model system that distinguishes vulnerability (learned helpless, LH) from resistance (non-learned helpless, NLH) to develop depression. Rats were exposed to inescapable shock on day 1 and day 7 and were tested for escape latency on day 14. Rats not given shock but tested for escape latency were used as tested control (TC). Plasma corticosterone levels were measured. Expression levels of various UPR associated genes were determined in hippocampus using qPCR. We found that the corticosterone level was higher in LH rats compared with TC and NLH rats. Expression of GRP78, GRP94, ATF6 and XBP-1 were significantly upregulated in LH rats compared with TC or NLH rats, whereas NLH rats did not show such changes. Expression levels of ATF4 and CHOP showed trends towards upregulation but were not significantly altered in LH or NLH group. Our data show strong evidence of altered UPR system in depressed rats, which could be associated with development of depressive behavior.